Upaya Mengoptimalkan Bandar Lurus Sebagai Saluran Drainase Utama Kawasan Air Pacah Kota Padang - Februarman, Februarman (Jurnal Bangunan, Konstruksi & Desain, 2024)
Almost every year, floods occur that inundate several areas in Padang City, one of which is the Air Pacah Area. Based on field observations, waterlogging occurs because the drainage channel network is unable to drain the water discharge that burdens it. This can occur due to narrowing, shallowing, garbage blockages and limited dimensions of the channel. This study aims to determine the water level elevation that occurs in the middle section of Bandar Lurus for the planned discharge of 10-year and 25-year return periods using HEC-RAS software. Based on rainfall data and channel geometry obtained from the Water Resources and Construction Service of West Sumatra Province, and with a catchment area of ​​Bandar Lurus of 9.82 km2, the planned flood discharge values ​​for 10-year and 25-year return periods are 46.53 m3/s and 66.48 m3/s respectively. The results of the HEC-RAS simulation, for both discharge values, indicate that there will be an overflow along the middle section of Bandar Lurus, the flow of which will burden the Bandar Maransi channel and the box culvert located near the Siti Rahmah Islamic Hospital. To avoid flooding in the Air Pacah area, it is necessary to accelerate the normalization of the middle section of Bandar Lurus so that the resulting flow does not burden other channels.